2007
DOI: 10.18388/abp.2007_3166
|View full text |Cite
|
Sign up to set email alerts
|

Response of Acanthamoeba castellanii mitochondria to oxidative stress.

Abstract: The purpose of this study was to examine the effects of oxidative stress caused by hydroperoxide (H(2)O(2)) in the presence of iron ions (Fe(2+)) on mitochondria of the amoeba Acanthamoeba castellanii. We used isolated mitochondria of A. castellanii and exposed them to four levels of H(2)O(2) concentration: 0.5, 5, 15, and 25 mM. We measured basic energetics of mitochondria: oxygen consumption in phosphorylation state (state 3) and resting state (state 4), respiratory coefficient rates (RC), ADP/O ratios, memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 29 publications
(32 reference statements)
1
10
2
Order By: Relevance
“…It is revealed by no changes in respiratory rates, ∆Ψ values and coupling parameters found in the presence of the alternative oxidase inhibitor BHAM. In contrast, using similar conditions (1 min incubation with 0.5-25 mM H 2 O 2 , in the presence of Fe 2+ ) Trocha and Stobienia (2007) observed a significant increase in both state 3 and state 4 respiration accompanied by a considerable decrease in ∆Ψ values and coupling parameters. The results described by those authors seem to be inconsistent, as the increase in phosphorylating respiration found for H 2 O 2treated mitochondria (e.g., a 3-fold increase for 25 mM H 2 O 2 ) was accompanied by an enormous cytochrome c release.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…It is revealed by no changes in respiratory rates, ∆Ψ values and coupling parameters found in the presence of the alternative oxidase inhibitor BHAM. In contrast, using similar conditions (1 min incubation with 0.5-25 mM H 2 O 2 , in the presence of Fe 2+ ) Trocha and Stobienia (2007) observed a significant increase in both state 3 and state 4 respiration accompanied by a considerable decrease in ∆Ψ values and coupling parameters. The results described by those authors seem to be inconsistent, as the increase in phosphorylating respiration found for H 2 O 2treated mitochondria (e.g., a 3-fold increase for 25 mM H 2 O 2 ) was accompanied by an enormous cytochrome c release.…”
Section: Discussionmentioning
confidence: 74%
“…The aim of the present work was to establish the basic energetic parameters of amoeba A. castellanii mitochondria respiring with malate and their response to oxidative stress caused by H 2 O 2 in the presence of Fe 2+ . Our aim was to verify the results obtained recently by Trocha and Stobienia (2007) with isolated A. castellanii mitochondria treated for a short time (1 min) with increasing concentrations of H 2 O 2 (up to 25 mM) in the presence of Fe 2+ . The puzzling results reported by those authors included unexpectedly quite high values of coupling parameters obtained with malate under control conditions (ADP/O ratio of 2.9 and RCR of 11) and inconsistent changes observed after 1 min incubation of mitochondria with H 2 O 2 , i.e., up to a 3-fold increase in phosphorylating respiration accompanied by an enormous cytochrome c release, as well as a decrease in the coupling parameters.…”
Section: Introductionmentioning
confidence: 62%
See 3 more Smart Citations